2015-08-16  math 

NOTE001よりメモ

$$ (a + b)(a - b) = a^2 - b^2 \qquad \text{和と差の積は$2$乗の差(恒等式)} $$

$$ \begin{align*} (a + b)(a - b) &= (a + b)a - (a + b)b && \qquad \text{$(a + b)$を、$(a - b)$の$a$と$b$に掛けた} \\ &= aa + ba - (a + b)b && \qquad \text{$(a + b)a$の部分を展開した} \\ &= aa + ba - (ab + bb) && \qquad \text{$(a + b)b$の部分を展開した} \\ &= aa + ba - ab - bb && \qquad \text{カッコを外した} \\ &= aa + ab - ab - bb && \qquad \text{$ba$を$ab$にした} \\ &= aa - bb && \qquad \text{$ab - ab$は$0$になって消える} \\ &= a^2 - bb && \qquad \text{$aa$を$a^2$と書いた} \\ &= a^2 - b^2 && \qquad \text{$bb$を$b^2$と書いた} \\ \end{align*} $$

 2015-08-16  math